Benthic biota of Chilean fjords and channels in 25 years of cruises of the National Oceanographic Committee - Aldea Venegas, Cristian Leonardo; Novoa, Leslie; Acuna, Maria Paz; Acevedo-Romo, Ignacia; Bravo, Francisco (My University, 2023)
The CIMAR program (Marine Research Cruises to Remote Areas) run by the Chilean Navy through the National Oceanographic Committee has been developed since 1995, focused on Chilean fjord and channel zones (similar to 41-56 degrees S; "CIMAR-Fjords") and Chilean remote islands ("CIMAR-Islands"). Samples and data was collected on biotic and abiotic variables on all these cruises, both from the water column and benthos. Our work standardizes, compiles, and summarizes the published information on benthic organisms for twenty-one CIMAR-Fjords cruises developed in the first 25 years of the program, plus the Southern Ice Fields Cruise 1995 (precursor of the CIMAR program), which includes the distribution, abundance and geographic location of cruises sampling stations. The data set includes 8,854 records from 880 different localities, corresponding to 1,225 species from 24 different phyla (four kingdoms) and more than 150,000 individuals. Only two cruises did not record any benthic sampling. The fjords and channels of Chilean Patagonia have high biodiversity, so we hope that our data set will serve as a baseline for ecological studies and ecosystem conservation.
Keywords: Fjord; Benthos; Biota